2022
DOI: 10.55056/etq.35
|View full text |Cite
|
Sign up to set email alerts
|

Virtual learning environments: major trends in the use of modern digital technologies in higher education institutions

Abstract: The article reveals the features of development and integrated implementation of virtual learning environment with the use of modern digital technologies in the learning process of higher education. The article summarizes the interpretation of the concept of "virtual learning environment". Virtual learning environment can be interpreted as an immersive online learning environment that has a methodologically integrated learning system, provides an open interactive dynamic learning process in cyberspace using mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Additionally, Abumandour (2021), ensure that the physical learning locations have the necessary resources to facilitate blended learning, including adequate seating, video equipment, and other resources (Nafisah, 2022). Kovtoniuk et al, 2022 also indicated that this includes spending money on hiring and training technical support people to enable professors and students to utilize blended learning technology. These technical support teams are crucial to making sure that students enjoy blended learning and can overcome any technological obstacles they may encounter said by (Alrashdi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Abumandour (2021), ensure that the physical learning locations have the necessary resources to facilitate blended learning, including adequate seating, video equipment, and other resources (Nafisah, 2022). Kovtoniuk et al, 2022 also indicated that this includes spending money on hiring and training technical support people to enable professors and students to utilize blended learning technology. These technical support teams are crucial to making sure that students enjoy blended learning and can overcome any technological obstacles they may encounter said by (Alrashdi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To help professors and students effectively use blended learning technology, this includes spending money on technical support staff recruitment and training (Kovtoniuk et al, 2022). To ensure that students have a pleasant experience with blended learning and can get past any technological challenges they might run into, these technical support teams are essential (Alrashdi et al, 2021).…”
Section: Support and Collaborationmentioning
confidence: 99%
“…Digitalization of education has become the subject of many scientific studies devoted to the theoretical and methodological foundations of distance education (Myroslav I. Zhaldak [8], Yukhum I. Mashbyts [9], Illia O. Teplytskyi [10], Svitlana V. Shokaliuk [11]); blended learning (Liudmyla I. Bilousova [12], Kateryna P. Osadcha [13], Iryna S. Mintii [14], Serhiy O. Semerikov [15], Yurii V. Tryus [16]); development of the informational and educational environment (Mariia A. Kislova [17], Kateryna I. Slovak [18], Liubov F. Panchenko [19], Kateryna V. Vlasenko [20], Olena O. Lavrentieva [21], Mariana M. Kovtoniuk [22], Tetiana A. Vakaliuk [23], Yuriy L. Kuchyn [24], Oleksandr Yu. Burov [25]); and information and communication competence of teachers in the conditions of a cloud-oriented educational environment (Kateryna V. Vlasenko [26], Iryna V. Lovianova [27], Tetiana A. Vakaliuk [28], Nataliia V. Morze [29], Mykhailo V. Moiseienko [30]); adaptive cloud-oriented system of training and professional development of teachers of secondary school (Hanna B. Varina [31], Yuliya H. Nosenko [32], Kateryna P. Osadcha [33]); determination of teachers readiness and need of digital tools and ICT during quarantine (Oksana V. Ovcharuk [34]); digital transformation of education (Tetiana V. Sych [7], Olga P. Pinchuk [35], Oksana V. Ovcharuk [36], Andrey V. Pikilnyak [37]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A cloud-based environment for organizing the learning process through flipped learning should provide e-support for students' and teachers' activities at the stages "before class", "in class", and "after class". The notion and possibility of using a learning environment are considered by Burov [5], Demianenko [8], Ivaniuk [14], Kovtoniuk et al [17], Vakaliuk [36], Voloshynov et al [38].…”
Section: Theoretical Backgroundmentioning
confidence: 99%